Impact of Cassia acutifolia Infusion on Glucose Levels in Obesity and Diabetes Rat Model - Raffoul-Orozco Abdel Kerim; Ávila-González Ana Elisa; Barajas-Vega Jessica Lucía; Rodríguez-Razón Christian Martín; García-Cobián Teresa Arcelia; Ramírez-Lizardo Ernesto Javier; Rubio Arellano Edy David (Korean Pharmacopuncture Institute, 2017)
Objectives: The aim of this study was to investigate the effects of Cassia acutifolia on the obesity and the glucose levels in a rat model of obesity and diabetes. Methods: By random selection, 36 Wistar male rats were divided in two control groups, the positive and the negative control groups, and into four experimental groups receiving different infusions of Cassia acutifolia in water ad libitum. Results: The results revealed a statistically significant anti-obesogenic effect (P = 0.02), although this was not considered clinically significant. Additionally, Cassia acutifolia lowered the glucose levels by 30 mg/dL to 90 mg/dL (P = 0.05). However, we observed adverse effects in the liver, a two-fold increase in transaminase levels (P = 0.002), and in the kidneys, decreased creatinine levels (P = 0.001), and these adverse effects had no viable explanation. Conclusion: Cassia acutifolia has anti-hyperglycemic effects in obese diabetic rats. However, Cassia acutifolia also has adverse effects, so it should not be administered to patients.